A retrospective survey of the quality of reports and their correlates among randomized controlled trials of immunotherapy for Guillain–Barré syndrome. (August 2013) - Lu, Liming; Luo, Gaoquan; Xiao, Fang
Aim: This study aims to assess the quality of reports and their correlates in randomized controlled trials (RCTs) of immunotherapy for Guillain–Barré syndrome (GBS).Methods: A search was performed in multiple databases of reports published between April 1992 and November 2012. Reporting quality was assessed by items of the Consolidated Standards of Reporting Trials (CONSORT) 2010 Statement. An overall quality score (OQS) and a key methodological index score (MIS) were calculated for each trial. Factors associated with OQS and MIS were then identified.Results: A total of 19 RCTs were included in the full text. The median OQS was 7.0, with a range of 1–10. However, the quality of reporting in items of 'flow chart' and 'ancillary analyses' was poor with a positive rate of less than 40%. The median MIS was 0 with a range of 0–2. Twelve (63.2%) did not report any of the three key methodological items. Specifically, the mean OQS increased by approximately 2.73 for manuscripts published in the New England Journal of Medicine, The Lancet, Pediatrics and Neurology (95% CI: 0.35–5.12; p < 0.05). Multivariate linear regression and the Poisson regression model could not be presented as the number of included trials was too small.Conclusion: The reporting quality in RCTs on immunotherapy for GBS was poor, which indicated that reporting in RCTs of immunotherapy for GBS needed substantial improvement in order to meet the guideline of the CONSORT Statement.